Desenvolvimento e caracterização de nanodispersões líquido-cristalinas contendo AICIPc para uso em terapia fotodinâmica em linhagem celular de câncer de pele - Borges, Márcia Hermínia Pinheiro (2024)
Non-melanoma skin cancer is one of the most common tumors in the world. Photodynamic therapy (PDT) is currently a non-invasive therapeutic option for the treatment of skin cancer and skin cancer precursor lesions. Chloro-aluminum phthalocyanine (AlClPc) is a second-generation photosensitizer that has been studied for application in PDT. AlClPc is a hydrophobic molecule and tends to self-aggregate in aqueous and biological environments, which impairs its therapeutic action. Encapsulation in nanocarriers can contribute to the maintenance of the monomeric structure and consequently improve its effectiveness in biological environments. In this sense, the association of nanotechnology with AlClPc, through encapsulation in nanocarriers, can contribute to its stability and effectiveness. Liquid crystalline nanodispersions (NLC) have been widely studied as drug nanocarriers, due to their unique nanostructure that presents desired characteristics for drug administration through various routes. In this work, NLCs based on oleic acid (AO), Phosal 75SA®, containing or not D-α-Tocopherol polyethylene glycol 1000 succinate (TPGS) in PBS buffer containing poloxamer P407 (P407), with subsequent incorporation of AlClPc into the Selected NLC (NLC-AlClPc). The obtained NLC-AlClPc was characterized, showing a nanometric size (152.3 ± 1.93 nm), PDI and encapsulation efficiency (EE%) of 0.231 ± 0.009 and 70.26 ± 3.87%, respectively, and stability for 30 days. NLC-AlClPc showed morphology compatible with a hexagonal phase in polarized light microscopy, which was confirmed in small-angle X-ray diffraction (SAXS). In the in vitro skin penetration test, NLC-AlClPc showed better penetration into the deep layers of the skin than the AlClPc-propylene glycol control. Cytotoxicity and phototoxicity at 630nm were also evaluated in two cell lines using the MTT method. NLC-AlClPc showed greater phototoxicity in the A431 tumor line than free AlClPc and greater phototoxicity in A431 in relation to the L929 fibroblast cell line. The proposed formulation developed, in addition to being innovative, presented satisfactory results in the characterizations carried out, as well as being able to improve, in vitro, the skin penetration of AlClPc and the photodynamic action in tumor lineage.